Risk Premium and Foreign Direct Investment in Africa - Effah-Mensah, D. (University of Ghana, 2015)
Canonical finance theory holds that capital should move to the assets with the greater risk premium. Does foreign direct investment (FDI) move to countries with a higher country risk premia? We address this question in this study. We proxied country risk premium as the difference between the equity risk premium of an Africa country and the equity risk premium of US, sovereign bond spread and we measured foreign direct investment as the foreign inflows scaled by gross domestic product. Using a dynamic panel model and data from African countries from 2000-2012, we find that country risk premium has a positive and statistically significant effect on FDI irrespective of how the risk premium is measured. Variables commonly associated with FDI in the literature such as infrastructure availability and log of labor availability showed varying statistical significance, varying with the measurement of country risk premium. Alas, can we say international investors in the last decade are hunting for premia?
Thesis (MPhil) - University of Ghana, 2015
Keywords: Risk; Foreign Direct Investment; Africa; Risk Premium